Virtual tools and cybercrime in judicial proceedings in San José de Cúcuta - Contreras Manrique, Rocío de Belén; Valero Bencardino, Juvenal; Carvajal Sandoval, José Vicente; Espinosa Bohórquez, Luz Marina; Contreras Manrique, Liliana (2025)
This book focuses on the special research topic of virtual tools and cybercrimes in criminal and family law proceedings in the Cúcuta judicial circuit. It seeks to summarize the criminal category, emphasizing computer expertise as a legal-evidentiary debate and its implementation in the courtroom. This is achieved through interdisciplinary interaction, as they involve different branches of law.Computer law and legal informatics emerge internationally and nationally due to new technologies emanating from electronic media; their origin lies in the digital evidence acquired through information that navigates through electronic commerce and, in turn, through telecommunications in cyberspace.Law and Systems Engineering come together to analyze the experimental situation of expert witnesses in criminal and family law trials from the perspective of computer forensics, as an evidentiary technique discussed in courtrooms. Evidence always has a source, production, or practice regulated by law, and in turn, leads the judge to conclude that facts, conduct, or claims exist for the proper and effective administration of justice.Legal scholars—in this case, criminal and family law—and computer science experts observe that in certain legal disputes, the assistance of an expert specialized in ICT, cybernetics, or virtuality, social media, WhatsApp, electronic signatures, and, in general, everything that requires a computer professional to provide evidence in a judicial process is required.
Keywords: Virtual tools; Crimes; Computing; Right; Judicial proceedings; Saint Joseph of Cúcuta